A method for preparing a fuel cell membrane electrode catalyst layer
By mixing the catalyst particles and resin particles into powder without using solvents, and adhering to the film under the action of electric field and electrostatic. The catalytic layer is formed by heating and hot pressing, which solves the problems of membrane swelling and high cost in the traditional method, and achieves a more efficient and environmentally friendly catalytic layer preparation.
Patent Information
- Application Number
- CN202211617907.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-12-15
- Publication Date
- 2025-03-14
- Estimated Expiration
- 2042-12-15
AI Technical Summary
The preparation method of traditional fuel cell membrane electrode catalytic layer requires the use of solvents, which leads to membrane swelling, environmental pollution, additional energy consumption and high preparation costs.
Using a preparation method without solvent, a uniform catalytic layer is formed by mixing the catalyst particles and resin particles into a catalytic layer powder, and the powder is flattened and attached to the proton exchange membrane under the action of electric field and electrostatic, and a uniform catalytic layer is formed by heating and hot pressing.
The swelling problem of the membrane is avoided, environmental pollution and additional energy consumption are reduced, preparation costs are reduced, and the uniformity and performance of the catalytic layer are improved.
Smart Images

Figure BDA0004002033010000101 
Figure BDA0004002033010000111 
Figure HDA0004002033020000011
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of fuel cells, and in particular relates to a method for preparing a fuel cell membrane electrode catalyst layer. Background Art
[0002] The membrane electrode is the core component of the fuel cell. Its structure consists of a proton exchange membrane, a catalyst layer and a gas diffusion layer. The proton exchange membrane is used to transmit protons required for the electrochemical reaction, while the catalyst layer is used to catalyze the electrochemical reaction. The catalyst / proton exchange membrane assembly formed by the combination of the two is the core component of the membrane electrode. The traditional methods for preparing the membrane electrode catalyst layer mainly include spraying, transfer and scraping. The spraying method is to spray the slurry made of catalyst and resin solution on the surface of the proton exchange membrane with a spray gun, and then dry to form a catalyst layer; the transfer method is to coat the slurry made of catalyst and resin solution on the transfer substrate, and then dry to form a catalyst layer, and finally transfer the catalyst layer on the transfer substrate to the proton exchange membrane by hot pressing; and the scraping method is to scrape the slurry made of catalyst and resin solution directly on the surface of the proton exchange membrane, and then dry to form a catalyst layer. It can be seen that the above traditional membrane electrode catalyst layer preparation methods all require the use of solvents to disperse the catalyst particles and resin components, and the use of solvents will inevitably lead to membrane swelling problems. In addition, since the solvent component does not participate in the formation of the catalytic layer, it needs to be dried and volatilized during the preparation process. Therefore, on the one hand, this brings certain environmental pollution problems, and on the other hand, it also leads to additional energy consumption and increases the preparation cost of the catalytic layer. Summary of the invention
[0003] In order to solve the problems existing in the prior art, the present invention provides a method for preparing a fuel cell electrode catalyst layer. The method of the present invention abandons the use of solvents, improves the swelling problem of the membrane caused by using solvents to disperse catalyst particles and resin components, reduces environmental pollution, solvent waste and extra energy consumption, and reduces costs.
[0004] In order to achieve the above object, the technical solution adopted by the present invention is:
[0005] The present invention provides a method for preparing a fuel cell membrane electrode catalyst layer, comprising the following steps:
[0006] (1) mixing catalyst particles and resin particles to form a catalyst layer powder;
[0007] (2) applying a voltage to the catalyst layer powder and the transfer substrate, wherein the catalyst layer powder is connected to the negative electrode and the transfer substrate is connected to the positive electrode, and then the charged catalyst layer powder is swept across the surface of the transfer substrate, so that the catalyst layer powder is flattened and adhered to the surface of the transfer substrate under the action of the electric field and static electricity;
[0008] (3) The membrane is heated, and the powder attached to the transfer substrate is transferred and bonded to the two sides of the membrane by relying on the viscosity of the resin in the catalyst layer powder to form a catalyst layer;
[0009] (4) The catalytic layers on both sides of the membrane are cured by hot pressing.
[0010] The uniformity of the membrane electrode catalyst layer is one of the key factors affecting its performance. The uniform distribution of the powder on the surface of the transfer substrate in step (2) of the preparation method and the uniform transfer of the powder from the transfer substrate to the membrane in step (3) are conducive to the formation of a uniform catalyst layer in the subsequent steps.
[0011] In step (2) of the preparation method, charging the powder will cause it to have a certain negative charge, and under the induction of the electric field, a positive charge will be induced on the transfer substrate, so that when the powder sweeps over the surface of the transfer substrate, the powder is spread and adhered to the surface of the transfer substrate, and the adsorption amount is related to the charging voltage; in order to make the powder adsorbed on the surface of the transfer substrate as evenly distributed as possible, the surface of the transfer substrate should be as flat as possible, and the width of the slit of the powder bin should also be consistent;
[0012] In step (3) of the preparation method, the viscosity of the film and the resin component in the powder will increase when heated, so that the powder can adhere to the surface of the film to form a catalytic layer and complete the transfer; in order to ensure the transfer effect of the powder to the film surface, the film and the transfer substrate need to be in close contact, which is conducive to uniform heating of the film and the resin material, thereby improving the transfer effect.
[0013] Further, the catalyst is selected from one of Pt / C or platinum black;
[0014] The particle size of the catalyst particles is 1-20 nm;
[0015] The resin is selected from one of Nafion-H, PVDF or PTFE;
[0016] The particle size of the resin particles is 0.1-10 μm;
[0017] The mass ratio of the catalyst to the resin in the catalyst layer powder is 10:1-1:10;
[0018] Preferably, the mass ratio of the catalyst to the resin in the catalyst layer powder is 2:1-1:5.
[0019] Furthermore, the membrane is selected from one of Nafion-H membrane and PBI membrane.
[0020] Due to the preparation process, the particle sizes of the catalyst and resin particles are not a specific value, but have a certain particle size distribution: for catalyst particles, the upper limit of the distribution range is lower than 20nm and the lower limit is higher than 1nm; for resin particles, the upper limit of the distribution range is lower than 10μm and the lower limit is higher than 0.1μm;
[0021] The powder used to prepare the catalytic layer is made by fully mixing the catalyst and the resin particles. During the mixing process, due to the electrostatic effect, a coating structure of an inner resin layer and an outer catalyst layer is formed, so that the catalyst particles can be exposed as much as possible while being bonded by the resin to achieve their catalytic function;
[0022] Based on the preparation method, there is a ratio requirement between the catalyst and the resin: when the amount of the catalyst is too much, the excess catalyst is easily lost because it cannot be bonded by the resin; when the amount of the catalyst is too little, it will cause a waste of the resin.
[0023] Furthermore, in step (2), the voltage applied to the catalyst layer powder and the transfer substrate is 1-20 kV;
[0024] Preferably, the voltage applied to the catalyst layer powder and the transfer substrate is 10-20 kV.
[0025] In step (2), the speed at which the catalyst layer powder is swept across the surface of the transfer substrate is 5-30 cm / min;
[0026] Preferably, the speed at which the catalytic layer powder sweeps across the surface of the transfer substrate is 10-15 cm / min.
[0027] In step (2) of the preparation method, the charging voltage of the powder and the speed at which the catalyst layer powder sweeps across the transfer substrate surface (corresponding to the speed at which the powder bin slit sweeps across the transfer substrate surface when the device described in the embodiment performs transfer) determine the adsorption density of the powder on the transfer substrate, thereby affecting the transfer amount of the powder per unit area of the membrane surface: a decrease in the charging voltage or an increase in the sweeping speed will reduce the adsorption density of the powder on the transfer substrate, and conversely an increase in the charging voltage or a decrease in the sweeping speed will increase the adsorption density of the powder on the transfer substrate. Therefore, in actual operation, the amount of powder (or catalyst) loaded on the membrane can be controlled by these two parameters;
[0028] On the other hand, in step (2) of the preparation method, there are certain requirements for the charging voltage of the powder and the speed at which the catalytic layer powder is swept across the surface of the transfer substrate: when the charging voltage is too low, the powder is not firmly adsorbed on the transfer substrate and is easily disturbed by the airflow, while when the sweeping speed is too high, empty spots without adsorbed powder particles are likely to appear on the transfer substrate, both of which are not conducive to the uniform distribution of powder particles on the transfer substrate; on the contrary, when the charging voltage is too high or the sweeping speed is too low, the adsorption density of the powder is too high, which will cause the powder on the surface of the transfer substrate to fly out prematurely when approaching the membrane, resulting in a poor transfer effect.
[0029] Further, in step (3), the heating temperature of the membrane is 80-120°C;
[0030] Preferably, the film is heated to a temperature of 100-120°C.
[0031] In step (3) of the preparation method, heating the membrane can increase its viscosity, which is necessary for the bonding and transfer process of powder particles on its surface; however, heating the membrane at too high a temperature will cause it to deform or even decompose, resulting in a decrease in the final membrane electrode performance.
[0032] Further, the temperature of the hot pressing is 80-200°C;
[0033] Preferably, the temperature of the hot pressing is 100-120°C;
[0034] The hot pressing pressure is 0.1-5.0MPa;
[0035] Preferably, the hot pressing pressure is 0.5-1.0 MPa;
[0036] The heat pressing time is 1-60min;
[0037] Preferably, the heat pressing time is 5-20 minutes.
[0038] The purpose of step (4) of the preparation method is to further solidify the powder bonded to the membrane surface, so that the formed catalytic layer is more solid and the loss of reactants under scouring in actual working conditions is reduced;
[0039] On the other hand, compared with the conventional wet method for preparing the membrane electrode catalyst layer, a major advantage of the preparation method of the present invention is that the macroporous structure of the powder particles can be retained to a large extent, which is beneficial to the transmission of the reaction materials during the actual battery operation. Therefore, the hot pressing process in step (4) of the preparation method is another key point of the entire preparation method, and there are certain requirements for the parameters of the hot pressing process:
[0040] (1) The resin component in the powder softens when heated, thus playing a bonding role. If the heating temperature is too low, the bonding effect becomes poor, causing the catalyst particles to easily peel off. If the heating temperature is too high, the membrane will deform or even decompose, resulting in a decrease in the final membrane electrode performance.
[0041] (2) Applying a certain amount of pressure while heating is beneficial to fully heat the resin particles in the powder and improve the bonding effect, but excessive pressure will destroy the pore structure between the powder particles, resulting in a decrease in the final membrane electrode performance;
[0042] (3) The duration of the hot pressing process should be selected so that the powder particles and the film are fully heated and firmly bonded.
[0043] Furthermore, a device for preparing a fuel cell membrane electrode catalyst layer using the preparation method comprises a high voltage generator, a temperature controller, a discharger, a powder bin, a transfer roller and a heating roller, wherein the transfer roller and the heating roller are both metal rollers with an insulating layer on the roller surface;
[0044] The high voltage end (negative pole) of the high voltage generator is connected to the powder bin; the grounding end (positive pole) of the high voltage generator is respectively connected to the discharger and the metal roller inside the transfer roller; the powder bin and the discharger are respectively located on the roller surfaces on opposite sides of the transfer roller; the roller surface of the transfer roller and the roller surface of the heating roller are in contact with each other; the temperature controller is connected to the heating roller; a film is provided between the transfer roller and the heating roller, and the film is tangent to the transfer roller and the heating roller.
[0045] Furthermore, a heating wire and a thermocouple are provided inside the heating roller, and the temperature controller is provided with a heating interface and a temperature measuring interface, the heating interface is connected to the heating wire, and the temperature measuring interface is connected to the thermocouple.
[0046] Furthermore, the powder bin is a metal bin with a slit at the bottom, the discharger is a metal sheet with a flat surface; the discharger is located on one side of the film moving direction; the powder bin is located on the side away from the film moving direction;
[0047] The rotating shaft of the transfer roller and the rotating shaft of the heating roller are connected through gears, so that the transfer roller can drive the heating roller to rotate when rotating. The transfer roller and the heating roller rotate in opposite directions and the linear speeds of the roller surfaces of the two rollers are equal.
[0048] In the preparation device of the fuel cell membrane electrode catalyst layer, the function of the discharger is to eliminate the residual charge left on the surface of the transfer roller after the powder is transferred to the membrane, and to prevent the surface of the transfer roller wrapped by the insulating layer from reducing the amount of powder adsorption due to carrying negative charge; the surface of the discharger metal sheet needs to be as flat and smooth as possible, and the good fit between it and the transfer roller can achieve a good discharge effect on the surface of the transfer roller.
[0049] The discharger, the outer shell of the powder bin, the transfer roller and the metal roller inside the heating roller should have good conductivity and be made of stainless steel;
[0050] The insulating layer covering the transfer roller and the heating roller should have a certain anti-stickiness, and the material is polytetrafluoroethylene;
[0051] The outer diameter of the transfer roller is 5-10 cm;
[0052] The outer diameter of the heating roller is 2-5 cm.
[0053] Furthermore, a method for preparing a fuel cell membrane electrode catalyst layer using the device comprises the following steps:
[0054] (1) Mix the catalyst and resin particles into powder and place it in a powder bin;
[0055] (2) Turn on the temperature controller to heat the heating roller and keep it at a constant temperature, and then send one end of the film to the contact point between the transfer roller and the heating roller;
[0056] (3) Turn on the high voltage generator to charge the powder in the powder bin, and then rotate the transfer roller and the heating roller. The rotation direction is such that the surface of the transfer roller passes through the powder bin, the heating roller and the discharger in sequence. At this time, the powder in the powder bin is continuously covered on the surface of the transfer roller by the electric field, and is transported by the transfer roller and adhered to one side of the membrane under the heating of the heating roller to form a catalytic layer.
[0057] (4) feeding one end of the film with the catalytic layer on one side into the contact area between the transfer roller and the heating roller, with the side with the catalytic layer facing the heating roller, and repeating step (3) to form a catalytic layer on the other side of the film;
[0058] (5) The membrane with the catalytic layer on both sides is subjected to hot pressing treatment to solidify the catalytic layer.
[0059] In step (3) of the preparation method, the viscosity of the resin components in the film and the powder will increase when heated by the heating roller, and the powder will adhere to the surface of the film under the extrusion effect at the contact point between the transfer roller and the heating roller. In order to ensure the transfer effect of the powder to the film surface, the surface of the heating roller should be as flat as possible, and the rotating axes of the heating roller and the transfer roller should be as parallel as possible. This not only makes the degree of extrusion of the film at the contact point consistent, but also helps to evenly heat the film.
[0060] In summary, the method for preparing the fuel cell membrane electrode catalyst layer of the present invention has the following characteristics in principle and device structure:
[0061] (1) Unlike the carbon powder used in laser printing, the catalyst in the powder used in the preparation method has good electrical conductivity and accounts for a relatively high proportion of the powder, so it can be directly charged, and the charging roller used to charge the transfer roller is omitted in the device structure;
[0062] (2) The preparation method is to prevent the film from being damaged by electric field breakdown on the one hand, and to transfer the powder adsorbed on the transfer roller to the film surface as much as possible at one time on the other hand, to prevent the residual powder from affecting the transfer effect. Therefore, the viscosity of the film itself is used to transfer the powder to the film surface under heating conditions;
[0063] (3) In the preparation method, since the membrane itself does not have a porous structure formed by fibers in paper and the heating temperature of the membrane cannot be too high, the membrane and the heating roller must be tightly fitted during heating to make the formed catalytic layer more solid.
[0064] The present invention also provides a fuel cell membrane electrode catalyst layer prepared according to the above-mentioned preparation method. The membrane electrode catalyst layer is formed by resin particles coated with catalyst particles on the surface, which are bonded and stacked together. There is an interlaced pore structure between the resin particles, which improves the transmission capacity of the reaction materials in the catalyst layer, and the catalyst covered on the outer layer of the resin has a higher utilization rate.
[0065] The present invention also provides a fuel cell membrane electrode catalyst layer prepared by the above preparation method, wherein the membrane electrode catalyst layer is formed by mutually bonding and stacking resin particles coated with catalyst particles on the surface, and has a staggered pore structure between the resin particles.
[0066] The present invention also provides the use of the above fuel cell membrane electrode catalyst layer in a membrane electrode.
[0067] Compared with the prior art, the method for preparing the fuel cell membrane electrode catalyst layer provided by the present invention has the following advantages:
[0068] (1) Compared with the traditional wet method, the preparation method does not use solvent to disperse the resin material and the catalyst, thus avoiding the swelling problem of the membrane;
[0069] (2) Since the preparation method does not use a solvent, the extra energy consumption caused by the solvent evaporation step is avoided, thereby reducing the preparation cost;
[0070] (3) Since the solvent components in the traditional wet method will eventually volatilize, the preparation method is greener and more environmentally friendly;
[0071] (4) The powder particles containing the resin and the catalyst are directly transported to the membrane surface by electrostatic action. Therefore, the catalyst layer of the membrane electrode prepared by the preparation method can retain the macroporous structure of the powder particles to a large extent, which is conducive to the transmission of the reaction materials under actual working conditions;
[0072] (5) The catalyst in the membrane electrode catalyst layer is distributed in the outer layer of the resin, which is conducive to its contact with the reaction materials and improves the catalyst utilization rate. BRIEF DESCRIPTION OF THE DRAWINGS
[0073] Figure 1 The present invention is a schematic diagram of the device used in the method for preparing the membrane electrode catalyst layer. In the figure: 1. high voltage generator; 2. temperature controller; 3. discharger; 4. powder bin; 5. transfer roller; 6. heating roller; 7. membrane.
[0074] Figure 2 The SEM image of the catalyst / membrane assembly CCM-3 (side) including the fuel cell electrode catalyst layer.
[0075] Figure 3 It is the performance test result (polarization curve) of a single fuel cell installed with catalyst / membrane assembly CCM-1.
[0076] Figure 4 These are the stability test results of a single-cell fuel cell installed using the catalyst / membrane assembly CCM-1. DETAILED DESCRIPTION
[0077] In order to further illustrate the present invention, the following embodiments are listed according to experimental results in combination with the accompanying drawings, but they do not limit the scope of the invention defined in the claims.
[0078] Example 1
[0079] According to Figure 1 The device for preparing the membrane electrode catalyst layer is shown as follows:
[0080] The transfer roller 5 is a metal roller with an insulating layer on the roller surface, and the heating roller 6 is a metal roller with an insulating layer on the roller surface and a heating wire and a thermocouple inside. The transfer roller 5 and the heating roller 6 are connected by gears, so that when the transfer roller 5 rotates, it can drive the heating roller 6 to rotate, the two rotation directions are opposite and the linear speeds of the two surfaces are equal. A film 7 is provided between the transfer roller 5 and the heating roller 6, and the film 7 is tangent to the transfer roller 5 and the heating roller 6. The heating roller 6 is connected to the temperature controller 2, specifically, the temperature controller 2 is provided with a heating interface and a temperature measuring interface, the heating interface is connected to the heating wire inside the heating roller 6, and the temperature measuring interface is connected to the thermocouple interface inside the heating roller 6.
[0081] The roller surface of the transfer roller 5 is also connected to the discharger 3 and the powder bin 4 respectively. The discharger 3 is a metal sheet with a flat surface, and the powder bin 4 is a metal bin with a slit at the bottom. The roller surface of the transfer roller 5 fits with the slit at the bottom of the distribution bin 4. The slit is a discharge port. The discharger 3 is perpendicular to the film 7, and the discharge direction of the powder bin 4 is perpendicular to the film 7. The discharger 3 and the discharge direction of the powder bin 4 are parallel to each other. The powder bin 4 is located at a position ahead of the transfer roller 5 and the heating roller 6 where the transfer roller 5 fits together along the rotation direction of the transfer roller 5, and the discharger 3 is located at a position delayed from the transfer roller 5 and the heating roller 6 where the transfer roller 5 fits together along the rotation direction of the transfer roller 5. The outer shell of the powder bin 4 is connected to the high voltage end (negative pole) of the high voltage generator 1, and the ground end (positive pole) of the high voltage generator 1 is connected to the discharger 3 and the metal roller inside the transfer roller 5.
[0082] Example 2
[0083] This example illustrates the use of the preparation method to prepare a fuel cell membrane electrode catalyst layer.
[0084] 1) First, according to Example 1, Figure 1 The device for preparing the membrane electrode catalyst layer is installed. The transfer roller and the heating roller used are stainless steel cylinders with a diameter of 5 cm and 2 cm respectively, which are coated with a polytetrafluoroethylene layer (i.e., the copper side wall of the stainless steel cylinder is coated with a polytetrafluoroethylene layer). Then, Pt / C (Pt content is 40wt.%) catalyst and Nafion-H resin (particle size distribution is 0.7-5.0μm) are mixed evenly in a mass ratio of 3:1 to form a powder and placed in a powder bin;
[0085] 2) Turn on the temperature controller and set the temperature to 100°C. After the temperature stabilizes, turn on the high voltage generator and set the output voltage to 10kV to charge the powder. Then, feed one end of the Nafion-H membrane into the joint between the transfer roller and the heating roller.
[0086] 3) rotating the transfer roller and the heating roller at a surface linear speed of 10 cm / min, so that the powder is transferred from the transfer roller to one side of the Nafion-H membrane and adhered to form a catalytic layer under the heating of the heating roller;
[0087] 4) The Nafion-H membrane with a catalytic layer on one side obtained in step 3) is again fed into the bonding area between the transfer roller and the heating roller, with the side with the catalytic layer facing the heating roller, and step 3) is repeated to form a catalytic layer on the other side of the Nafion-H membrane;
[0088] 5) The Nafion-H membrane with the catalytic layer transferred on both sides is placed on a hot pressing table for hot pressing. The hot pressing temperature is 120° C., the hot pressing pressure is 1.0 MPa, and the hot pressing time is 10 min. The prepared catalyst / membrane assembly is obtained, which is recorded as CCM-1.
[0089] Example 3
[0090] This example illustrates the use of the preparation method to change the ratio of catalyst to resin to prepare a fuel cell membrane electrode catalyst layer as a comparison with Example 2.
[0091] A catalyst / membrane assembly was prepared in the same manner as in Example 2, except that the mass ratio of catalyst to Nafion resin in step 1) was 5:1 instead of 3:1, and was designated as CCM-2.
[0092] Example 4
[0093] This example illustrates the use of the preparation method to change the ratio of catalyst to resin to prepare a fuel cell membrane electrode catalyst layer as a comparison with Example 2.
[0094] A catalyst / membrane assembly was prepared in the same manner as in Example 2, except that the mass ratio of catalyst to Nafion resin in step 1) was 1:1 instead of 3:1, and was designated as CCM-3.
[0095] The catalyst / membrane module CCM-3 was characterized by SEM to check the morphology. The results are shown in the attached figure. Figure 2 As shown, it can be seen that the skeleton structure of the electrode catalyst layer is formed by resin particles bonded to each other. The particles are stacked to form an interlaced pore structure, and the catalyst particles with relatively small particle size are attached to the surface of the resin particles with relatively large particle size, so that the catalyst particles can be exposed as much as possible while being bonded by the resin in order to realize their catalytic function.
[0096] Example 5
[0097] This example illustrates the use of the preparation method to change the heating temperature of the membrane during transfer to prepare a fuel cell membrane electrode catalyst layer, as a comparison with Example 2.
[0098] A catalyst / membrane assembly was prepared in the same manner as in Example 2, except that the temperature controller in step 2) was set to 80° C. instead of 100° C., and was designated as CCM-4.
[0099] Example 6
[0100] This example illustrates the use of the preparation method to change the heating temperature of the membrane during transfer to prepare a fuel cell membrane electrode catalyst layer, as a comparison with Example 2.
[0101] A catalyst / membrane assembly was prepared in the same manner as in Example 2, except that the temperature controller in step 2) was set to 120° C. instead of 100° C., and was designated as CCM-5.
[0102] Example 7
[0103] This example illustrates the use of the preparation method to change the charging voltage of the powder during transfer to prepare a fuel cell membrane electrode catalyst layer, as a comparison with Example 2.
[0104] A catalyst / membrane assembly was prepared in the same manner as in Example 2, except that the output voltage of the high voltage generator in step 2) was set to 5 kV instead of 10 kV, and was designated as CCM-6.
[0105] Example 8
[0106] This example illustrates the use of the preparation method to change the charging voltage of the powder during transfer to prepare a fuel cell membrane electrode catalyst layer, as a comparison with Example 2.
[0107] A catalyst / membrane assembly was prepared in the same manner as in Example 2, except that the output voltage of the high voltage generator in step 2) was set to 15 kV instead of 10 kV, and was denoted as CCM-7.
[0108] Example 9
[0109] This example illustrates the use of the preparation method to change the charging voltage of the powder during transfer to prepare a fuel cell membrane electrode catalyst layer, as a comparison with Example 2.
[0110] The catalyst / membrane assembly was prepared in the same manner as in Example 2, except that the output voltage of the high voltage generator in step 2) was set to 20 kV instead of 10 kV, and was denoted as CCM-8.
[0111] Example 10
[0112] This example illustrates the use of the preparation method to change the hot pressing temperature to prepare a fuel cell membrane electrode catalyst layer as a comparison with Example 2.
[0113] A catalyst / membrane assembly was prepared in the same manner as in Example 2, except that the hot pressing temperature in step 5) was 100° C. instead of 120° C., and was designated as CCM-9.
[0114] Embodiment 11
[0115] This example illustrates the use of the preparation method to change the hot pressing temperature to prepare a fuel cell membrane electrode catalyst layer as a comparison with Example 2.
[0116] The catalyst / membrane assembly was prepared in the same manner as in Example 2, except that the hot pressing temperature in step 5) was 110° C. instead of 120° C., and was designated as CCM-9.
[0117] Example 12
[0118] This example illustrates the use of the preparation method to change the hot pressing pressure to prepare a fuel cell membrane electrode catalyst layer as a comparison with Example 2.
[0119] The catalyst / membrane assembly was prepared by the same preparation method as in Example 2, except that the hot pressing pressure in step 5) was 0.1 MPa instead of 1.0 MPa, and was denoted as CCM-11.
[0120] Embodiment 13
[0121] This example illustrates the use of the preparation method to change the hot pressing pressure to prepare a fuel cell membrane electrode catalyst layer as a comparison with Example 2.
[0122] The catalyst / membrane assembly was prepared in the same manner as in Example 2, except that the hot pressing pressure in step 5) was 0.5 MPa instead of 1.0 MPa, and was designated as CCM-12.
[0123] Embodiment 14
[0124] This example illustrates the use of the preparation method to change the hot pressing pressure to prepare a fuel cell membrane electrode catalyst layer as a comparison with Example 2.
[0125] The catalyst / membrane assembly was prepared by the same preparation method as in Example 2, except that the hot pressing pressure in step 5) was 2.0 MPa instead of 1.0 MPa, and was denoted as CCM-13.
[0126] Embodiment 15
[0127] This example illustrates the use of the preparation method to change the hot pressing pressure to prepare a fuel cell membrane electrode catalyst layer as a comparison with Example 2.
[0128] The catalyst / membrane assembly was prepared in the same manner as in Example 2, except that the hot pressing pressure in step 5) was 3.0 MPa instead of 1.0 MPa, and was designated as CCM-14.
[0129] Example 16
[0130] This example illustrates the use of the preparation method to change the hot pressing time to prepare a fuel cell membrane electrode catalyst layer as a comparison with Example 2.
[0131] The catalyst / membrane assembly was prepared in the same manner as in Example 2, except that the hot pressing time in step 5) was 1 min instead of 10 min, and was designated as CCM-15.
[0132] Embodiment 17
[0133] This example illustrates the use of the preparation method to change the hot pressing time to prepare a fuel cell membrane electrode catalyst layer as a comparison with Example 2.
[0134] The catalyst / membrane assembly was prepared in the same manner as in Example 2, except that the hot pressing time in step 5) was 5 min instead of 10 min, and was designated as CCM-16.
[0135] Embodiment 18
[0136] This example illustrates the use of the preparation method to change the hot pressing time to prepare a fuel cell membrane electrode catalyst layer as a comparison with Example 2.
[0137] The catalyst / membrane assembly was prepared in the same manner as in Example 2, except that the hot pressing time in step 5) was 20 min instead of 10 min, and was designated as CCM-17.
[0138] Embodiment 19
[0139] This example illustrates the performance test of the fuel cell catalyst / membrane assembly prepared by the preparation method.
[0140] The catalyst / membrane assemblies CCM-1 to CCM-17 prepared in Examples 2-18 were cut and hot-pressed together with the diffusion layer and the frame into membrane electrode assemblies, which were installed on a single fuel cell (CCM effective area of 2.0×2.5 cm 2 ), and then install the single battery on the fuel cell test bench for performance testing. The test conditions are: the positive electrode side intake is air, the pressure is 0.1MPa, and the flow rate is 800mL / min, the negative electrode side intake is hydrogen, the pressure is 0.1MPa, and the flow rate is 200mL / min, the battery is kept at a constant temperature of 80℃, and the temperature of the positive and negative electrode humidification tanks is 80℃ (100% humidification). At the beginning of the test, first set the above related parameters, turn on the electronic load after stabilization, and set the output current density to 1000mA / cm 2 The membrane electrode was activated for 6 hours. After the activation process was completed, the polarization curve was measured. Taking the catalyst / membrane assembly CCM-1 as an example, its polarization curve is shown in the attached figure. Figure 3 As shown. The open circuit voltage (corresponding to current density of 0), 500mA / cm 2 Corresponding voltage and 1000mA / cm 2 The corresponding voltage results are shown in the following table:
[0141]
[0142]
[0143] Embodiment 20
[0144] This example illustrates the stability test of a single fuel cell installed using the catalyst / membrane assembly CCM-1.
[0145] The catalyst / membrane assembly CCM-1 prepared in Example 2 was cut and hot-pressed together with the diffusion layer and frame into a membrane electrode assembly and installed on a single fuel cell (CCM effective area 2.0×2.5 cm 2 ), and then install the single battery on the fuel cell test bench for performance testing. The test conditions are: the positive electrode side intake is air, the pressure is 0.1MPa, and the flow rate is 800mL / min, the negative electrode side intake is hydrogen, the pressure is 0.1MPa, and the flow rate is 200mL / min, the battery is kept at a constant temperature of 80℃, and the temperature of the positive and negative electrode humidification tanks is 80℃ (100% humidification). At the beginning of the test, first set the above related parameters, turn on the electronic load after stabilization, and set the output current density to 1000mA / cm 2 The membrane electrode was activated for 6 hours. After the activation process was completed, the output current density was maintained at 1000 mA / cm 2 , continue for 120 hours, record the battery output voltage every 2 hours, the results are as shown in the attached Figure 4 As shown, it can be seen that the membrane electrode having the electrode catalyst layer prepared according to the preparation method of the present invention has good stability.
Claims
1. A method for preparing a fuel cell membrane electrode catalyst layer, characterized in that: The steps include: (1) mixing catalyst particles and resin particles to form a catalyst layer powder; (2) applying a voltage to the catalyst layer powder and the transfer substrate, wherein the catalyst layer powder is connected to the negative electrode and the transfer substrate is connected to the positive electrode, and then the charged catalyst layer powder is swept across the surface of the transfer substrate, so that the catalyst layer powder is flattened and adhered to the surface of the transfer substrate under the action of the electric field and static electricity; (3) The membrane is heated, and the powder attached to the transfer substrate is transferred and bonded to the two sides of the membrane by relying on the viscosity of the resin in the catalyst layer powder to form a catalyst layer; (4) The catalytic layers on both sides of the membrane are cured by hot pressing.
2. The preparation method according to claim 1, characterized in that: The catalyst is selected from one of Pt / C and platinum black; The particle size of the catalyst particles is 1-20 nm; The resin is selected from one of Nafion-H, PVDF or PTFE; The particle size of the resin particles is 0.1-10 μm; The mass ratio of the catalyst to the resin in the catalyst layer powder is 10:1-1:10; The membrane is selected from one of a Nafion-H membrane and a PBI membrane.
3. The preparation method according to claim 1, characterized in that: In step (2), the voltage applied to the catalyst layer powder and the transfer substrate is 1-20 kV; In step (2), the speed at which the catalyst layer powder is swept across the surface of the transfer substrate is 5-30 cm / min; The heating temperature of the membrane in step (3) is 80-120°C. The temperature of the hot pressing in step (4) is 80-200°C; The hot pressing pressure in step (4) is 0.1-5.0 MPa; The time of hot pressing in step (4) is 1-60 min.
4. The preparation method according to claim 1, characterized in that: The device for preparing a fuel cell membrane electrode catalyst layer using the preparation method comprises a high voltage generator (1), a temperature controller (2), a discharger (3), a powder bin (4), a transfer roller (5) and a heating roller (6), wherein the transfer roller (5) and the heating roller (6) are both metal rollers with an insulating layer on the roller surface; The negative electrode of the high-voltage generator (1) is connected to the powder bin (4); the positive electrode of the high-voltage generator (1) is respectively connected to the discharger (3) and the metal roller inside the transfer roller (5); the powder bin (4) and the discharger (3) are respectively located on the roller surfaces on opposite sides of the transfer roller (5); the roller surface of the transfer roller (5) and the roller surface of the heating roller (6) are in contact with each other; and the temperature controller (2) is connected to the heating roller.
5. The preparation method according to claim 4, characterized in that: A film (7) is provided between the transfer roller (5) and the heating roller (6), and the film (7) is tangent to the transfer roller (5) and the heating roller (6); The heating roller (6) is provided with a heating wire and a thermocouple inside, and the temperature controller (2) is provided with a heating interface and a temperature measuring interface, the heating interface is connected to the heating wire, and the temperature measuring interface is connected to the thermocouple.
6. The preparation method according to claim 4, characterized in that: The powder bin (4) is a metal bin with a slit at the bottom, and the discharger (3) is a metal sheet with a flat surface; the discharger (3) is located on one side of the moving direction of the film (7); and the powder bin (4) is located on the side away from the moving direction of the film (7); The rotating shaft of the transfer roller (5) and the rotating shaft of the heating roller (6) are connected via gears, so that when the transfer roller (5) rotates, it can drive the heating roller (6) to rotate; the rotation directions of the transfer roller (5) and the heating roller (6) are opposite, and the linear speeds of the roller surfaces of the two rollers are equal.
7. The preparation method according to claim 4, characterized in that: The material of the discharger (3), the powder bin (4), the transfer roller (5) and the heating roller (6) includes stainless steel; The insulating layer on the roller surface of the transfer roller (5) and the heating roller (6) is made of polytetrafluoroethylene; The outer diameter of the transfer roller (5) is 5-10 cm; The outer diameter of the heating roller (6) is 2-5 cm.
8. The preparation method according to claim 4, characterized in that: The method for preparing a fuel cell membrane electrode catalyst layer using the device comprises the following steps: (1) Mix the catalyst and resin particles into powder and place it in a powder bin; (2) Turn on the temperature controller to heat the heating roller and keep it at a constant temperature, and then send one end of the film to the contact point between the transfer roller and the heating roller; (3) Turn on the high voltage generator to charge the powder in the powder bin, and then rotate the transfer roller and the heating roller. The rotation direction is such that the surface of the transfer roller passes through the powder bin, the heating roller and the discharger in sequence. At this time, the powder in the powder bin is continuously covered on the surface of the transfer roller by the electric field, and is transported by the transfer roller and adhered to one side of the membrane under the heating of the heating roller to form a catalytic layer. (4) feeding one end of the film with the catalytic layer on one side into the contact area between the transfer roller and the heating roller, with the side with the catalytic layer facing the heating roller, and repeating step (3) to form a catalytic layer on the other side of the film; (5) The membrane with the catalytic layer on both sides is subjected to hot pressing treatment to solidify the catalytic layer.
9. The fuel cell membrane electrode catalyst layer prepared by the preparation method according to any one of claims 1 to 8, characterized in that: The membrane electrode catalyst layer is formed by resin particles coated with catalyst particles on the surface being bonded and stacked together, and there is a staggered pore structure between the resin particles.
10. Use of the fuel cell membrane electrode catalyst layer according to claim 9 in a membrane electrode.
Citation Information
Patent Citations
Method for preparing fuel cell membrane electrode by reel-to-reel stable and continuous printing
CN110416558A